Fear God and keep his commandments: Foundation for a relationship with God - Cailing, Rolex M. (Review and expositor, 2018)
This article argues that the "fear of God" concept links the theology and ethics of Qoheleth and plays a pivotal role in the quest for life's meaning amidst its challenges. It explores what B. K. Waltke echoes as "the kernel and star of the whole book" and "the dominant note of the book."1 It offers a cursory study of the relationship between God and human beings and its connection to the concept of "fearing God." It concludes that the "fear of God" is foundational to a relationship with God, and for seeing life within the limits and bounds of God's sovereignty. The key to Qoheleth's realistic attitude to life occurs in his doctrine of God. He believes that the Creator of the world is intimately concerned with the details of human lives and determines the fate of every human creature. Like the book of Job and Proverbs, Qoheleth asserts that the "fear of God" is the beginning of wisdom.